Analisis Bauran Pemasaran Terhadap Penjualan Offline dan Online (Studi Kasus pada UMKM Pelaku Usaha Martabak di Kecamat Gunung Pati dan Tembalang) - Salsabilla, Nasywa; Fathonah, Siti; Astuti, Pudji (LPPM Universitas Negeri Jakarta, 2025)
Marketing mix is one of the strategies serves as a reference for sellers to influence consumers. This study aims to analyze the implementation of the marketing mix on offline and online sales of martabak MSMEs in Gunung Pati and Tembalang Districts, and to determine whether there is an effect of the marketing mix on offline and online sales of martabak MSMEs in these districts. The population in this study consisted of 30 martabak MSME actors in Gunung Pati and Tembalang Districts, selected using purposive sampling. Data collection techniques used in this study were observation, interviews, and questionnaires. The collected data were analyzed quantitatively using descriptive analysis, simple linear regression, and hypothesis testing (t-test) with SPSS IBM version 25. The results showed that the marketing mix variable had a significant effect of value 31% the sales variables. Analysis showed that the indicators of product, price, and place were in the very good category, indicating that the implementation of the marketing mix was already optimal. Conversely, the promotion indicator was in the sufficient category because it had not been implemented optimally. Overall, offline sales were more stable compared to online sales.